Influence of strontium and lanthanum simultaneous addition on microstructure and mechanical properties of the secondary Al-Si-Cu-Fe alloy - 唐鹏 李文芳 赵艳君 王康 李伟洲 詹锋 (Journal of rare earths, 2017)
In this paper, modification agents with different contents of Sr and La elements were added into Al-Si-Cu-Fe alloy and the effect on refinement of secondary phases and α-Al grain was investigated by optical microscopy, scanning electronic microscopy and X-ray diffractometry. Tensile testing was carried out to characterize the strength of the alloys. The XRD result indicated that Fe9LaSi4 and SrSi2 phases were formed after Sr and La elements were added in the alloys simultaneously. With the help of metallographic analysis techniques, the length of needle-like phases, mainly composed of eutectic Si and β-Fe, was quantified. And the secondary dendrite arm spacing（SDAS） of α-Al grain was also evaluated. The quantification results indicated that the modification agents with different contents of Sr and La elements showed varied refinement effects on the mean length of needle-like phases and SDAS value. When the addition amount increased, the length of needle-like phase and SDAS value were decreased. The minimum mean length of needle-like phases（Sr/La=1：1） and the SDAS value（Sr/La=1：5） were obtained by setting the addition amount of the modification agent at 0.12 wt.%. The yield strength of the alloy was related to the mean SDAS value, whilst the ultimate tensile strength, elongation and hardness values were related to the mean length of needle-like phase.